Performance of nanohydroxapatite in overcoming the acute renal failure induced by cisplatin in male rats - Maha Mohammed Farid Ahmed; Elsayed Fahim Elsayed Taha; Eman Ismaiel Abdelgawad (Cairo : Maha Mohammed Farid Ahmed, 2020)
A population of rats was divided into four groups: Group1 injected intrapretioneal with saline, Group2 injected intravenously weekly with 100 mg/kg b.w. for three weeks, Group3 injected i.p. once with 5 mg/kg b.w. CDDP and Group4 received CDDP plus nano-HAp. In tissues, DNA fragmentation, kim 1 and histopathological were performed. In serum, NGAL,TNF-Ü, MCP-1, IL-10, BUN, creatinine, Na and K were measured.The results revealed that uptake of CDDP caused acute kidney injury.The treatment with nano-HAp repaired efficiently the fragmented DNA and ameliorated the most of investigated parameters.The histopathological observation was in agreement with biochemical results.In conclusion, nano-HAp succeeded in handling the symptoms of AKI and produced a new hope for patients to get treatment safe, fast and effective
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Zoology
Issued also as CD
Keywords: Acute kidney injury; Cisplatin; Nanohydroxyapatite